Leiomyosarcoma in a dos - Zabid Yener; İsmail Alkan; Hayati Yüksel; Nazmi Atasoy (Eurasian Journal of Veterinary Sciences)
In this report, a case of leiomyosarcoma in a 3-years-old. male, crossbred dog was described, Mac-roscopically, the tumor mass was measured as 8x3x3 cm in dimensions and was located in the back region. Tumor was grayish-white colored, solitary, subcutan, and had a lobular structure. Microscopically, tumor composed of the neoplastic cells with abundant cytoplasma, blunt and central nucleus. Immunohislochemically, some tumor markers, such as smooth muscle actin, desmin. vimentin and S-100 protein were investigated, from these vimentin was found to be positive.